REVITALISASI PENDEDERAN IKAN PATIN DI KAMPUNG PATIN, DESA SUKAMANDIJAYA, KECAMATAN CIASEM, KABUPATEN SUBANG, JAWA BARAT - Budiardi, Tatag; Effendi, Irzal; Diatin, Iis; Hadiroseyani, Yani; Vinasyam, Apriana; Wahjuningrum, Dinamella; Astari, Belinda (Jurnal Abdi Insani, 2025)
The market demand for catfish for consumption is increasing, so it is necessary to increase its cultivation productivity. For this reason, an increase in the production of ready-to-stock seeds in the rearing ponds is carried out which can be achieved through improving the management of seeds, water, and feed. With the increase in production in Sukamandijaya Village, there are opportunities for expansion to a wider market, both nationally and for export. This can make Kampung Patin one of the leading centers in the freshwater fisheries industry in West Java. The purpose of this community service activities is to prepare human resources who are responsive to innovation progress and resilient in increasing the productivity of catfish cultivation, especially in the nursery segment. The activity was carried out from August to October 2024 with four stages, namely socialization and surveys, catfish nursery training, demonstrations and mentoring, and activity evaluation. The target of the activity was 30 members of the Fish Cultivation Group (Pokdakan) in Sukamandijaya Village, Ciasem, Subang, West Java. The catfish nursery revitalization activity has had a positive impact on farmers, especially in increasing knowledge and skills. Skills improvement includes the use of water quality measuring equipment, data recording and analysis, knowledge of water probiotics to improve water quality and feed probiotics to improve feed efficiency, and awareness of the importance of food safety through the introduction of herbal medicines for controlling fish diseases. Time constraints in training are a challenge in themselves, so they are carried out through monitoring activities and discussions via the internet so that farmers still get the guidance needed to apply the techniques that have been learned optimally.